Bridges to Student Success. Exemplary Programs, 2000 - National Association of Student Personnel Administrators, Inc.; National Association of Student Personnel Administrators, Inc. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This document describes seven programs that were recognized as exemplary by the National Association of Student Personnel Administrators in 2000. Convinced that experiential learning promotes intellectual development, the first college recognized, Alleghany College, developed student learning agreements to contribute to the education of the "whole person." Northeastern Illinois University's Partners for Success Program provides roughly 95 first-year minority students with one-on-one mentoring. At Portland State University, five hundred students annually participate in the Leadership for Courage course program. A collaboration between student affairs professionals and faculty, the effort meets general education requirements. To combat increasing incidences of inappropriate behavior by some students, the Rochester Institute of Technology formed the Student Behavior Consultation Team, a post-crisis response group that helps offending students maintain satisfactory academic progress. In Fall 1999, Texas Tech University began the TECHniques Center. This fee-for-service academic enhancement program provides support services to learning disabled undergraduates so that higher education is more attainable for them. Achieving a College Education is a collaborative partnership among Pima Community College, the University of Arizona, and the Pima/Santa Cruz County school districts to increase at-risk student high school gradation and college enrollment rates. Finally, Students Educating and Advocating for Diversity is a continual, proactive effort at the University of Kansas Medical Center. Its main activity, to date, is a discussion series among the university community. (MKA)
Availability: National Association of Student Personnel Administrators, 1875 Connecticut Ave., NW, Suite 418, Washington, DC 20009-5728. Tel: 202-265-7500; Web site: http://www.naspa.org.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; College Programs; College Students; Cultural Pluralism; High Risk Students; Higher Education; Student Personnel Services; Student Personnel Workers; National Assn of Student Personnel Administrators; Allegheny College PA -- Northeastern Illinois University -- Pima Community College AZ -- Portland State University OR -- Rochester Institute of Technology NY -- Texas Tech University -- University of Arizona -- University of Kansas; Reports, Descriptive